APLIKASI MOTIF ORNAMEN BATIK ABYORHOKOKAI PADA SEPATU SLIP ON APLIKASI MOTIF ORNAMEN BATIK ABYORHOKOKAI PADA SEPATU SLIP ON - Jiyestha, Ni Made Thesa; Nurhidayat, Martiyadi; Muttaqien, Teuku Zulkarnain (Telkom University, 2023)
Slip on shoes are shoe products that are widely used by the general public in various activities such as hangouts, style or traveling in various kinds of events. In formal and everyday events, some people choose to use slip on but with a simple and comfortable style. Shoes that are used in daily activities or in certain events, of course, the aesthetic value and beauty of the shoes a a shoe sill be considered. So that when used it will remain stylish and elegant. Slip on shoes as a shoe design that is simple and easy to use are the most popular choices for use in formal events and dailyactivities of the user. The results of the design of slip on shoes are expected to increase the beauty of the shoes with the combination of ornamental motifs from Abyorhokokai peacock batik and can be used especially by women in daily activities orformal events which of course remain comfortable when used due to the simple form of slip on shoes. Key words: slip on, batik abyorhokokai, ornament.